Performance Study of Monocrystalline Type Solar Panels for Street Lighting in Sibolga Area - Yuli Mafendro Dedet Eka Saputra; Mochamamd Tendi Noer Ramadhan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
In the Sibolga area, there is still a shortage of electricity supply, especially for street lighting, so accidents often occur, meanwhile there has a relatively large average solar radiation intensity is 4,784 Wh/m2/day so that potential for PLTS installation. This research aims to determine the performance of monocrystalline solar panels with the addition of a heatsink cooling fan in street lighting. The method used is an experimental. The test begins with the survey, potential calculation, design, testing, data collection and analysis. The solar panel used monocrystalline 10 WP with a heatsink cooling fan. The parameters are the panel temperature, voltage, and current from the solar panel. The results obtained are the temperature on the solar panel without heatsink cooling fan reaches 56.10°C with efficiency 11% and on the solar panel with heatsink cooling fan only gets 45.50°C with efficiency increases to 13%. This shows that the addition of a heatsink cooling fan has succeeded in cooling the temperature of the solar panels and increasing the efficiency level of solar panel performance for street lighting.